CRISPR/Cas inactivation of RECQ4 increases homeologous crossovers in an interspecific tomato hybrid. Issue 3 (30th September 2019) - de Maagd, Ruud A.; Loonen, Annelies; Chouaref, Jihed; Pelé, Alexandre; Meijer‐Dekens, Fien; Fransz, Paul; Bai, Yuling
Summary: Crossover formation during meiosis in plants is required for proper chromosome segregation and is essential for crop breeding as it allows an (optimal) combination of traits by mixing parental alleles on each chromosome. Crossover formation commences with the production of a large number of DNA double‐strand breaks, of which only a few result in crossovers. A small number of genes, which drive the resolution of DNA crossover intermediate structures towards non‐crossovers, have been identified in Arabidopisis thaliana . In order to explore the potential of modification of these genes in interspecific hybrids between crops and their wild relatives towards increased production of crossovers, we have used CRISPR/Cas9‐mutagenesis in an interspecific tomato hybrid to knockout RecQ4 . A biallelic recq4 mutant was obtained in the F1 hybrid of Solanum lycopersicum and S. pimpinellifolium . Compared with the wild‐type F1 hybrid, the F1 recq4 mutant was shown to have a significant increase in crossovers: a 1.53‐fold increase when directly observing ring bivalents in male meiocytes microscopically and a 1.8‐fold extension of the genetic map when measured by analysing SNP markers in the progeny (F2) plants. This is one of the first demonstrations of increasing crossover frequency in interspecific hybrids by manipulating genes in crossover intermediate resolution pathways and the first to do so by directed mutagenesis. Significance statement: Increasing crossover frequency during meiosis can speed up or simplify crop breeding that relies on meiotic crossovers to introduce favourable alleles controlling important traits from wild relatives into crops. Here we show for the first time that knocking out an inhibitor of crossovers in an interspecific hybrid between tomato and its relative wild species using CRISPR/Cas9‐mutagenesis results in increased recombination between the two genomes.